Carotenoids: how effective are they to prevent age-related diseases? - Tan, Bee Ling; Mohd Esa, Norhaizan (MDPI, 2019)
Despite an increase in life expectancy that indicates positive human development, a new challenge is arising. Aging is positively associated with biological and cognitive degeneration, for instance cognitive decline, psychological impairment, and physical frailty. The elderly population is prone to oxidative stress due to the inefficiency of their endogenous antioxidant systems. As many studies showed an inverse relationship between carotenoids and age-related diseases (ARD) by reducing oxidative stress through interrupting the propagation of free radicals, carotenoid has been foreseen as a potential intervention for age-associated pathologies. Therefore, the role of carotenoids that counteract oxidative stress and promote healthy aging is worthy of further discussion. In this review, we discussed the underlying mechanisms of carotenoids involved in the prevention of ARD. Collectively, understanding the role of carotenoids in ARD would provide insights into a potential intervention that may affect the aging process, and subsequently promote healthy longevity.